Pengembangan dan Percepatan Pencapaian Tujuan Pemerataan Pembangunan Desa - Setyo R, Dedi; Salahudin, Salahudin (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to find out what we can know in planning equitable development in Indonesia. The research method used in this research is qualitative research. Data obtained through the website kemendes.go.id data processing using the Nvivo 12 application. The results of the study reveal the challenges of equitable distribution of village development. The rationale for village governance is diversity, participation, genuine autonomy, democratization and community empowerment. In the course of the state administration of the Republic of Indonesia, Villages have developed in various forms so that they need to be protected and empowered to become strong, advanced, independent, and democratic so that they can create a strong foundation in implementing governance and development towards a just, prosperous, and prosperous society. The village is the scope of government that broadly plays a role in carrying out regional development, equitable distribution of regional development is needed to support all community needs to achieve the constitutional mandate, namely equitable distribution of national development as the goal of the State of National Development of the State of Indonesia whose general goal is to realize the welfare of the people and its distribution throughout area, until now there are still many problems. One of the problems that are still encountered is the undeveloped border area between administrative regions within the State of Indonesia. So far, border areas are synonymous with rural areas, agricultural areas, poor areas, etc. For its development, a policy that is locally appropriate is needed, which is compiled based on the results of the identification of potential and development barriers in the border area. The National Development of the State of Indonesia is generally aimed at realizing the welfare of people's lives in a fair and equitable manner throughout the territory of the Republic of Indonesia, both those living in rural areas (rural areas) and urban areas (urban areas). and its distribution throughout its territory. The rationale for village governance is diversity, participation, genuine autonomy, democratization and community empowerment.